Proceedings of the International Conference on Chemical, Material and Food Engineering 2015
DOI: 10.2991/cmfe-15.2015.55
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Electrochemical Characterization of La Doping Co3O4 Super Capacitor Electrode Materials

Abstract: Abstract-An aqueous solution containing deionized water, cobalt nitrate hexahydrate (Co(NO 3 ) 2 ·6H 2 O), ethylene glycol (EG) and urea (NH 2 CONH 2 ) were reacted in an autoclave with hydrothermal reaction method at 180 o C for 20 h to generate precursors with 0.1%, 0.2%, 0.3%, 0.4% and 0.5% of La (NO3)3. Then the precursor was decomposed to cobalt oxide powders at 300-500 oC for 2h. The morphology and electrochemical properties of samples were characterized by powder X-ray diffraction (XRD), scanning electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…50 Chen et al reported Co 3 O 4 microspheres by using cobalt nitrate hexahydrate (Co(NO 3 ) 2 Á6H 2 O) and urea (NH 2 CONH 2 ) as reactants in a simple hydrothermal reaction for SC applications, showing a high capacitance of 372.7 F g À1 . 57 It is observed that most published works have focused on the different materials, synthesis parameters like temperature during reaction, deposition current, and reaction time, which affects the material morphology, fabrication of devices, and their potential applications; however, the effect of the different metal ratio is rarely reported in the literature. 6 Variation in the metal ratio significantly affects the morphology of synthesized nanostructures and in turn the electrochemical performance of the electrodes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 Chen et al reported Co 3 O 4 microspheres by using cobalt nitrate hexahydrate (Co(NO 3 ) 2 Á6H 2 O) and urea (NH 2 CONH 2 ) as reactants in a simple hydrothermal reaction for SC applications, showing a high capacitance of 372.7 F g À1 . 57 It is observed that most published works have focused on the different materials, synthesis parameters like temperature during reaction, deposition current, and reaction time, which affects the material morphology, fabrication of devices, and their potential applications; however, the effect of the different metal ratio is rarely reported in the literature. 6 Variation in the metal ratio significantly affects the morphology of synthesized nanostructures and in turn the electrochemical performance of the electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…50 Chen et al reported Co 3 O 4 microspheres by using cobalt nitrate hexahydrate (Co(NO 3 ) 2 ·6H 2 O) and urea (NH 2 CONH 2 ) as reactants in a simple hydrothermal reaction for SC applications, showing a high capacitance of 372.7 F g −1 . 57…”
Section: Introductionmentioning
confidence: 99%